Dynamic Behavior and Fatigue Damage Evolution of Sandstone under Uniaxial Cyclic Loading - Yidan Sun; Yu Yang; Min Li (Shock and Vibration)
The mechanical response characteristics of sandstone specimens under different stress amplitudes and loading frequencies were tested by a TAW-2000 rock triaxial testing machine. The characteristics of the stress-strain curve and the evolution process of strain damage under cyclic loading are analyzed. Based on creep theory and the disturbance state concept, a theoretical model between the axial compressive strain, axial compressive stress, and cycle number is established. The results show that there exists an upper threshold value of stress in cyclic loading above which the specimen will be damaged. As peak stress increases, the energy loss and irreversible deformation caused by damage gradually increase. When loading to an unstable peak stress under cyclic loading, the fatigue damage of sandstone under cyclic loading undergoes three characteristic stages: the initial stage; the stable stage; and the accelerated failure stage. The parameters of the strain damage model based on the disturbance state concept of sandstone are identified by test data, and the rationality of the model is validated by comparing theoretical values with experimental measurements.